Preferensi Media Pembelajaran dan Hasil Belajar Mahasiswa Generasi Z dalam Pendidikan Pemasaran Layanan Kesehatan: Peran Modul, PowerPoint, dan Media Kombinasi - Jeki Pornomo; Yasinta Indah Widyaningsih; Irfan Kurniawan (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Learning media selection is an important pedagogical issue in higher education. This study examined the association between students’ learning media preferences and answer scores in a healthcare marketing course. A quantitative observational design was used involving 304 students. Learning media preference was categorized into module, PowerPoint, combined module and PowerPoint, and other media. The primary outcome was answer score, while course rating and perceived interest were analyzed as descriptive indicators of learning experience. Descriptive statistics, group-based score comparison, multicollinearity assessment using variance inflation factor, and linear regression were applied. The combined-media group was used as the reference category in the regression model. Module-based learning was the most frequently preferred medium (38.5%), followed by combined module and PowerPoint use (30.6%) and PowerPoint-only preference (25.0%). Students achieved a high mean answer score of 83.22, while course rating was also high at 4.68 out of 5, and perceived interest was reported by nearly all respondents. PowerPoint-preferring students showed the highest descriptive mean score (84.55), followed by module-preferring students (82.99) and combined-media students (82.36). Regression analysis indicated that module preference was not significantly associated with answer score, while PowerPoint preference showed a positive but non-significant trend. Learning media preference alone did not significantly explain differences in student answer scores. The findings suggest that media format may be less important than pedagogical alignment, learner engagement, self-regulated learning, and instructional design quality. Future research should examine how media preference interacts with learning strategy, engagement, cognitive load, and course design in healthcare management education.